2009
DOI: 10.1038/ki.2008.508
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori infection in long-term hemodialysis patients

Abstract: Patients on hemodialysis often have gastrointestinal complications; however, it is unclear if Helicobacter pylori infection is present in these patients. Here we determined the prevalence of H. pylori infection in 539 Japanese hemodialysis patients by measuring serum anti-H. pylori IgG antibodies. Endoscopy was performed on 299 of these patients and the results were compared to 400 patients with normal renal function who had also undergone endoscopy and sero-testing. A second cohort of 478 dialysis patients, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
110
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(121 citation statements)
references
References 59 publications
(45 reference statements)
4
110
1
1
Order By: Relevance
“…However, recent consensus shows that the prevalence of H. pylori infection in chronic renal failure patients receiving peritoneal or hemodialysis to be equal or lower compared with the subjects with normal renal function in various different geographic populations irrespective of the presence/absence of gastric symptoms. [8][9][10][11] In our study, only 2 out of 30 patients with CKD (one on hemodialysis), who had OGD biopsy, showed H. pylori infection. The prevalence of infection decreases as dialysis periods progressed, in particular within the first 4 years after the start of treatment, suggesting that hemodialysis treatment, but not uremia, plays a role in the lower prevalence of H. pylori infection.…”
mentioning
confidence: 51%
“…However, recent consensus shows that the prevalence of H. pylori infection in chronic renal failure patients receiving peritoneal or hemodialysis to be equal or lower compared with the subjects with normal renal function in various different geographic populations irrespective of the presence/absence of gastric symptoms. [8][9][10][11] In our study, only 2 out of 30 patients with CKD (one on hemodialysis), who had OGD biopsy, showed H. pylori infection. The prevalence of infection decreases as dialysis periods progressed, in particular within the first 4 years after the start of treatment, suggesting that hemodialysis treatment, but not uremia, plays a role in the lower prevalence of H. pylori infection.…”
mentioning
confidence: 51%
“…Moreover, the prevalence of H. pylori infection in hemodialysis patients is significantly lower (27.5%) compared with non-hemodialysis chronic renal failure patients (56.0%), [18] and the prevalence in individuals with normal renal function, are similar with patients receiving hemodialysis treatment for less than the 1-year period [17]. These data suggest that hemodialysis treatment, but not uremia by chronic renal failure itself, plays a role in the lower prevalence of H. pylori infection.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, in the investigation of 539 Japanese hemodialysis patients with treatment in a mean period of 8.4 to 0.3 years, the prevalence of H. pylori infection was reported to be 48.6%, which was significantly lower than in dyspepsia patients with normal renal function (78.5%) and individuals with the normal renal function receiving health checkup (69.4%) [17]. Moreover, the prevalence of H. pylori infection in hemodialysis patients is significantly lower (27.5%) compared with non-hemodialysis chronic renal failure patients (56.0%), [18] and the prevalence in individuals with normal renal function, are similar with patients receiving hemodialysis treatment for less than the 1-year period [17].…”
Section: Discussionmentioning
confidence: 94%
“…Our study showed that patients with CKD and a history of UGIB had a 2-fold higher risk of UGIB. In addition, H. pylori infection has been associated with a higher risk of UGIB (23,24), and H. pylori eradication therapy decreases the risk of recurrent UGIB (25). Forty-two (1.4%) patients were receiving H. pylori eradication therapy; this therapy did not significantly affect UGIB risk.…”
Section: Discussionmentioning
confidence: 99%